HUBUNGAN DISIPLIN KERJA GURU DENGAN KETERAMPILAN MENGELOLA KELAS TK DI KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Nita Andryani; Ria Novianti; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the correlation between teacher’s work discipline and classroom management skills in kindergarten at the districts Rambah Hilir, district Rokan Hulu. The study population was all kindergarten teachers in the district Rambah Hilir with as many as 73 people. Determination of the number of subjects in this study using saturated sampling technique is sampling technique when the members of the population used as a sample in this study as many as 73 people. The method used is the technique of Pearson Chi Square to see t the correlation between teacher’s work discipline and classroom management skills in kindergarten at the districts Rambah Hilir, district Rokan Hulu. The data collection techniques used is through a scale in the form of a questionnaire. Based on test results obtained by the hypothesis that there is a significant positive the correlation between teacher’s work discipline and classroom management skills in kindergarten at the districts Rambah Hilir, district Rokan Hulu. It can be seen from the results of Chi Square coefficient between labor discipline teachers with classroom management skills of x2 count = 45,792a and x2 table = 3.841. Then the x2 count > x2 table (45.792> 3.841), then h0 is rejected and ha accepted. It means there is a positive and significant the correlation between teacher’s work discipline and classroom management skills in kindergarten at the districts Rambah Hilir, district Rokan Hulu.Key word : Discipline Work, Classroom Management Skills